2014
DOI: 10.1590/s1984-29612014095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a spray formulation on the reproductive parameters of a susceptible population of Rhipicephalus (Boophilus) microplus

Abstract: The number of studies emphasizing the possible damage that acaricidal spray formulations can cause on engorged female ticks' reproductive parameters is small. The present study evaluated the deleterious effects of a spray formulation (dichlorvos 60% + chlorpyrifos 20%) on the reproductive parameters of a susceptible population of Rhipicephalus (B.) microplus females, using the Stall Test. The ticks were allocated randomly to treatments according to the mean numbers of females detached from each cow on days -3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…As described by Holdsworth et al (2006), for testing products with a slower onset of action, such as benzoylphenyl ureas, selective acaricides (IGR), draft product labels must indicate the period of time required to kill a designated percentage of ticks on treated ruminants, based on valid scientific data. Under such criteria, and considering previous studies which demonstrated that 2.5 mg/kg fluazuron takes about 14 days to present its satisfactory effects against this cattle tick (Cruz et al, 2014;Gomes et al, 2015), R. (B.)…”
Section: Criteria For Diagnosis Of Susceptibility or Resistant/low Sumentioning
confidence: 94%
See 1 more Smart Citation
“…As described by Holdsworth et al (2006), for testing products with a slower onset of action, such as benzoylphenyl ureas, selective acaricides (IGR), draft product labels must indicate the period of time required to kill a designated percentage of ticks on treated ruminants, based on valid scientific data. Under such criteria, and considering previous studies which demonstrated that 2.5 mg/kg fluazuron takes about 14 days to present its satisfactory effects against this cattle tick (Cruz et al, 2014;Gomes et al, 2015), R. (B.)…”
Section: Criteria For Diagnosis Of Susceptibility or Resistant/low Sumentioning
confidence: 94%
“…Rhipicephalus (Boophilus) microplus is considered one of the most important ectoparasites in cattle industry (Cruz et al, 2014). It has a wide geographical distribution, comprehending tropical and subtropical regions situated between latitude parallels 32 • north and 35 • south, comprising countries of Latin America, Africa, Asia and Oceania (Wharton, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…The Rhipicephalus (Boophilus) microplus is one of the most widely distributed ticks in the world, is the main cattle ticks, being responsible for major losses in Brazilian cattle (Seixas et al, 2012), causing direct and indirect damage to animal health, limiting considerably the productivity (Cruz et al, 2014). The parasite control relies mainly on the use of chemical acaricides that are produced from a limited set of molecules.…”
Section: Theoretical Review 21 Boophilus Microplusmentioning
confidence: 99%